Can Malaysia Escape the Middle-Income Trap? A Strategy for Penang - Yusuf, Shahid (The World Bank, 2009)
How can Penang upgrade and diversify its economy? This paper addresses this question using a number of methodologies that have been developed for assessing competitiveness and identifying the direction of future industrial evolution. The results show that although Penang was successful in attracting foreign direct investment to the electronics industry, this has not translated into a deepening of industrial capabilities or the nurturing of innovation capacity in Penang. No large Malaysian firms in Penang have taken the lead in innovation and there is little new entry by local firms, despite incentives provided by local and national governments are generous. Universiti Sains Malaysia, the principal university in Penang, is contributing through provision of skills, and it is beginning to multiply university industry linkages. However, the university's research activities are too limited and too diffuse to significantly initiate innovation by local industry. Under the current circumstances, and given its relatively small size, Penang will have to try much harder to strengthen its competitive advantage in its most important industry -electronics- through actions that build research capital. It will also have to increase its efforts to develop the potential of other value-adding activities, such as medical services and tourism. A strategy focused on localization economies is likely to be the most feasible option